PENGARUH DISIPLIN KERJA, KOMPENSASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT MITRA SINTERA DI KOTA BATAM - Kilvin, Kilvin; Siagian, Mauli (FEB Universitas Sam Ratulangi Manado, 2020)
This study has purpose to research the influence of work discipline, compensation and motivation on employee performance at PT Mitra Sintera by using a saturated sampling technique. The total sample of this study is 108. The data method was collected with a questionnaire. This research uses the validity and reliability test, the classic assumption test, analysis multiple linear regression and analysis coefficient of determination, t test and F test using by software program SPSS 25 version. In the results test for the coefficient of determination obtained from the work discipline, compensation and motivation variables have an effect of 16,4% on employee performance. In the results test for multiple linear regression obtained the work discipline influences the employee performance by 25,2%, the compensation influences the employee performance by 20,1% and the motivation influences the employee performance of 19,9%. In the results of t test obtained that the work discipline has partially significant effect on employee performance, the compensation has partially significant effect on employee performance and the motivation has partially significant effect on employee performance. While in the results of F test obtained work discipline, compensation and motivation together have simultaneously significant effect on employee performance.Â Keywords: Â Work Discipline, Compensation, Motivation, Employee Performance